Pseudoxanthoma Elasticum of the Skin with Involvement of the Oral Cavity. (18th May 2013) - Matsuo, Flávia Sayuri; Berbert, Alceu Luiz Camargo Villela; Mantese, Sônia Antunes de Oliveira; Loyola, Adriano Mota; Cardoso, Sérgio Vitorino; de Faria, Paulo Rogério
Abstract : Pseudoxanthoma elasticum (PXE) is an inherited multisystemic disease of elastic fibers that primarily affects the skin and retina. A case of primary PXE of the skin with late involvement of the upper lip is reported. A 55-year-old woman with a previous diagnosis of PXE affecting her skin developed a lesion on her lower lip. An oral examination identified a yellowish macule of undefined limits. A biopsy from her lip was taken and both light and transmission electron microscopies confirmed the presence of fragmented elastic fibers and calcifications on her mucosa, which was compatible with the diagnosis of oral PXE. Since the manifestation of oral PXE is rare in this region, dental practitioners must be aware that this systemic condition may produce oral lesions, which sometimes may mimic other benign diseases of the oral cavity like Fordyce granules. So, the establishment of an appropriate diagnosis is necessary to provide adequate information and attention to the patient.